Przemiany religijności w społeczeństwie polskim - Ma̜kosa, Paweł (Verbum vitae, 2024)
This article focuses on the transformations of religiosity within Polish society concerning self-declared affiliations, religious practices and moral principles, all framed within the context of Church activities. The study presents empirical analyses based on data obtained from research institutions and individual projects, highlighting differences between the general population and the youth demographic. The research findings confirm that dynamic secularisation predominantly affects the youth. The article also reflects on the possibility of the Church formulating an appropriate response to the identified challenges, although this issue remains open for further discussion.